La cioccolata e la noia. Cases e la letteratura italiana - Fichera, Gabriele (L'ospite ingrato, 2024)
This study attempts to individuate within Cesare Cases’s collected essays Patrie Lettere the fundamental interpretative lines with which the essayist read some moments of Italian literature of the 20th century, with particular attention to the novels of Gadda, Calvino and Morante. Starting from a sociological framework dominated by the antinomy between social “boredom” and revolutionary change, between the “staticity” of advanced areas and the political dynamism of depressed areas, the ways in which Cases, with the theoretical support of acute interlocutors such as Lukács, Benjamin and Szondi, found the tracks of this dialectic in the structures of the story, with particular attention to the objective instances expressed by the narrative voices, caught in their artistic camouflage, between epicness and parody, prolepsis and “responsibility”.